Boron-silicon-carbon-doped iron oxychloride materials, methods of making and using the same

CN122897416APending Publication Date: 2026-10-13JINING UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611012648.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-08
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

将其作为耐热助剂、补强填料或功能改性剂添加至硅橡胶体系中,可有效改善硅橡胶的界面结合状态,显著提升其耐高温性能、力学性能及热氧老化稳定性,解决了传统填料耐热效果有限、与硅橡胶相容性差、力学与耐热难以兼顾等问题,在高温硅橡胶材料领域具有重要的应用价值

Benefits of technology

1.本发明制备工艺简便高效,实用性强,解决了现有杂化材料制备步骤繁琐、反应条件苛刻、设备要求高的问题;本发明仅通过“研磨混合-搅拌混匀-高温煅烧”三步即可制得目标产物,无需复杂的催化剂、溶剂及后续提纯工艺;反应条件温和易控制,可实现规模化生产,降低制备成本。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122897416A_ABST
    Figure CN122897416A_ABST
Patent Text Reader

Abstract

The application discloses a boron-silicon-carbon doped ferric oxychloride material and a preparation method and application thereof, and belongs to the technical field of organic-inorganic hybrid materials. The technical scheme comprises the following steps: 1) taking an iron-based chloride and an organic boric acid compound, grinding and uniformly mixing, and placing the uniformly mixed material into a reactor; 2) adding phenyl chlorosilane into the reactor and uniformly mixing by stirring; and 3) calcining the material after mixing in the step 2) to obtain the boron-silicon-carbon doped ferric oxychloride material. The preparation process is simple, the obtained boron-silicon-carbon doped ferric oxychloride material can be used as a heat-resistant additive, a reinforcing filler or a functional modifier for silicone rubber, can effectively improve the high-temperature resistance of the silicone rubber without affecting the mechanical properties of the silicone rubber, and has a good application prospect in the field of high-temperature silicone rubber materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of organic-inorganic hybrid materials technology, specifically relating to a boron-silicon-carbon doped iron oxychloride material, its preparation method and application, which is particularly suitable for the heat resistance, reinforcement and aging stability modification of high-temperature silicone rubber materials, and can be widely used in the preparation of silicone rubber products under high-temperature environments. Background Technology

[0002] Silicone rubber, an elastomer with -Si-O- bonds as its main chain and organic groups as side groups, has been widely used in aerospace, new energy vehicles, electronics, rail transportation, and other fields due to its excellent high and low temperature resistance, weather resistance, ozone resistance, and physiological inertness. It plays an irreplaceable role, especially in sealing, insulation, and protection applications in high-temperature environments. Its main chain silicon-oxygen bond energy reaches up to 452 kJ / mol, significantly higher than carbon-carbon bonds, allowing silicone rubber to operate continuously in the 200–250°C range and withstand short-term temperatures above 300°C. However, with the continuous upgrading of industrial technology, high-end applications such as new energy vehicle power batteries, 5G base station heat dissipation modules, and aero-engine seals place higher demands on the high-temperature resistance, mechanical properties, and long-term aging stability of silicone rubber. Traditional silicone rubber can no longer meet the stringent high-temperature tolerance requirements of relevant standards.

[0003] To improve the overall performance of silicone rubber, the industry commonly uses the addition of functional fillers or hybrid modifiers. Among these, inorganic-organic hybrid materials are the preferred direction for silicone rubber modification due to their combination of the high thermal stability of inorganic materials and the good interfacial compatibility of organic materials. Currently, hybrid materials used for silicone rubber modification mainly include hybrids containing elements such as boron, silicon, titanium, and aluminum. Boron-containing hybrid materials can improve the heat resistance of silicone rubber by forming a stable boron-oxygen structure, while iron-containing compounds can inhibit the cyclization degradation of the silicone rubber main chain and excessive cross-linking of side methyl groups, further optimizing thermal stability. Phenyl-containing silicon-based materials can improve the interfacial compatibility between the hybrid material and the silicone rubber matrix, reduce filler agglomeration problems, and improve the modification effect.

[0004] However, existing borosilicate hybrid materials and iron-based modified materials are mostly single-element or dual-element hybrids, which have drawbacks such as limited improvement in thermal stability, insufficient interfacial compatibility, and complex preparation processes. Single borosilicate hybrid materials cannot simultaneously meet the dual requirements of heat resistance and reinforcement. Single iron-based modified materials have poor dispersion in silicone rubber matrices and are prone to agglomeration, leading to a decrease in the mechanical properties of silicone rubber. The preparation of some multi-element hybrid materials requires complex sol-gel methods or multi-step reaction processes, which have harsh reaction conditions, cumbersome processes, and high production costs. Moreover, the interfacial bonding between the resulting hybrid materials and silicone rubber is weak, which cannot fully exert the synergistic modification effect and is difficult to adapt to the application requirements of high-end high-temperature scenarios.

[0005] Furthermore, existing hybrid materials for modifying silicone rubber have significant performance shortcomings. For example, while some hybrid materials can improve heat resistance, they can lead to a decrease in the elasticity and toughness of silicone rubber. Other materials, although possessing some reinforcing effects, are prone to performance degradation after long-term aging at high temperatures, failing to meet long-term service requirements. Therefore, developing a hybrid material with a simple preparation process, mild conditions, good thermal stability and interfacial compatibility, and the ability to simultaneously achieve multiple modification effects on silicone rubber, including heat resistance, reinforcement, and aging stability, has become a pressing technical challenge in the field of inorganic-organic hybrid materials and silicone rubber modification. It also provides an urgent technical need for the research and application of high-end high-temperature silicone rubber products.

[0006] Chinese invention patent CN114958001B prepares ablation-resistant silicone rubber by compounding phenylsiloxane with iron compounds. Although iron and phenyl are introduced, boron is not included, and the BO-Si bond lacks the high-temperature stabilization and reinforcement effect on the silicone rubber main chain. Moreover, it is a simple physical compound system with weak interfacial bonding and insufficient long-term thermo-oxidative aging stability. Chinese invention patent CN115838477A prepares linear borosilicate polymers with octamethylcyclotetrasiloxane and boric acid / boronic acid esters, which are used as tackifiers for silicone rubber self-adhesive tapes. Although it has a borosilicate structure, the system does not contain iron and independent inorganic hybrid fillers. The degree of inorganic hybridization is low, the upper limit of reinforcement and heat resistance is limited, and the high-temperature long-term performance is poor. Therefore, the preparation of an inorganic-organic hybrid material that combines high-temperature resistance with effective increase in the strength of silicone rubber and good compatibility with the system has become a research hotspot in the industry. Summary of the Invention

[0007] This invention provides a boron-silicon-carbon doped iron oxychloride material, its preparation method, and its applications. The material is prepared by calcining a mixture of phenylchlorosilane, organoboronic acid compounds, and iron-based chlorides. The prepared boron-silicon-carbon doped iron oxychloride material exhibits synergistic effects from boron, silicon, oxygen, and iron, resulting in excellent thermal stability. When added to silicone rubber systems as a heat-resistant additive, reinforcing filler, or functional modifier, it effectively improves the interfacial bonding state of silicone rubber, significantly enhancing its high-temperature resistance, mechanical properties, and thermo-oxidative aging stability. This solves the problems of limited heat resistance, poor compatibility with silicone rubber, and difficulty in balancing mechanical properties and heat resistance found in traditional fillers, making it of significant application value in the field of high-temperature silicone rubber materials.

[0008] The technical solution of this invention is as follows: In the first aspect, a method for preparing boron-silicon-carbon doped iron oxychloride materials is disclosed, including the following steps: 1) Take iron-based chloride and organoboronic acid compounds, grind and mix them evenly, and put the evenly mixed material into the reactor; 2) Add phenylchlorosilane to the reactor and stir to mix thoroughly; 3) Calcine the mixed materials from step 2) to obtain boron-silicon-carbon doped iron oxychloride material.

[0009] Preferably, the molar ratio of the iron-based chloride, organoboronic acid compound and phenylchlorosilane is 1:(0.5-1.6):(0.8-1.2).

[0010] Preferably, the iron-based chloride is ferric chloride hexahydrate or ferrous chloride tetrahydrate.

[0011] Preferably, the organoboronic acid compound is one of phenylboronic acid, p-methylphenylboronic acid, and naphthaleneboronic acid.

[0012] Preferably, the phenylchlorosilane is one of diphenyldichlorosilane, phenyltrichlorosilane, and methylphenyldichlorosilane.

[0013] Preferably, the calcination temperature in step 3) is 180-280℃ and the time is 2-8h.

[0014] Preferably, the calcination temperature in step 3) is 230-250℃ and the time is 4-6h.

[0015] Secondly, the boron-silicon-carbon doped iron oxychloride material prepared by the aforementioned preparation method is disclosed.

[0016] Thirdly, the application of the boron-silicon-carbon doped iron oxychloride material in silicone rubber is disclosed.

[0017] This invention employs a solvent-free solid-phase low-temperature one-step synthesis system. The overall reaction is divided into three stages: solid-phase pre-crosslinking, silicon source hydrolysis and condensation, and low-temperature crystallization doping. The specific reaction mechanism is as follows: 1) Grinding and premixing stage: Take iron-based chloride (carrying water of crystallization), and organic boric acid compounds with dihydroxyl structure. During the grinding process, hydrogen bonding and dehydration condensation of trace solid phases occur in close solid-solid contact to generate Fe-OB covalently linked precursors, so as to achieve uniform dispersion of Fe and boron precursors at the molecular level and avoid local agglomeration of subsequent doping components.

[0018] 2) Silicon source composite stage: Phenylchlorosilane undergoes mild hydrolysis with trace amounts of crystal water in the system to generate silanol intermediates and release hydrogen chloride gas; silanol rapidly undergoes cross-dehydration condensation with B-OH and Fe surface hydroxyl groups in the system to construct Fe-OB-Si inorganic cross-linked framework, and phenyl groups are simultaneously anchored in the cross-linked network to complete the uniform composite of silicon and carbon precursors.

[0019] 3) The isothermal calcination stage is the core process in which the crystal phase and doping occur simultaneously: The iron-based chloride is completely dehydrated. Under the action of a sufficient chlorine source in the system, the iron-based chloride hydrolyzes to generate an orthogonal layered FeOCl matrix. The low temperature environment of about 240℃ can avoid the thermal decomposition of FeOCl and ensure the purity of the main crystal phase. B in the cross-linked backbone 3+ Si 4+ Partially replaces Fe in the FeOCl lattice 3+ This causes lattice distortion, generating a large number of oxygen vacancies and crystal defects; the remaining boron and silicon components are attached to the FeOCl layer interface as an amorphous boron-silicon-oxygen composite phase, constraining the layer stacking. The benzene rings in organoboronic acid compounds and phenylchlorosilanes undergo incomplete pyrolysis at low temperatures, removing small-molecule hydrocarbon volatiles and generating a thin layer of amorphous conductive carbon in situ. This carbon uniformly coats the crystals and fills the interlayer voids, forming hybrid bonds with boron and silicon to synergistically regulate the material's electron transport properties. The entire calcination process releases water, hydrogen chloride, and small-molecule aromatic hydrocarbon gaseous byproducts, leaving no solid impurities. The final product is a pure-phase substrate, a ternary uniformly doped and modified boron-silicon-carbon-doped iron oxychloride material.

[0020] Compared with the prior art, the present invention has the following advantages: 1. The preparation process of this invention is simple, efficient, and highly practical, solving the problems of cumbersome preparation steps, harsh reaction conditions, and high equipment requirements of existing hybrid materials. This invention can obtain the target product in just three steps: "grinding and mixing - stirring and homogenizing - high-temperature calcination", without the need for complex catalysts, solvents, and subsequent purification processes. The reaction conditions are mild and easy to control, enabling large-scale production and reducing preparation costs.

[0021] 2. The boron, silicon, and carbon doped iron oxychloride powder prepared by this invention has uniformly dispersed boron, silicon, and carbon doping components, and the powder has no obvious hard agglomerates. A fine and uniform powder can be obtained by simple grinding. When this filler is mixed with silicone rubber raw rubber, it can quickly and uniformly impregnate and disperse in the rubber matrix without causing a sharp increase in the viscosity of the system, effectively avoiding processing defects such as high extrusion molding resistance and uneven discharge. Under the premise of achieving the same heat resistance modification effect, silicone rubber filled with this filler will not have problems of tensile strength reduction or thixotropic degradation, simultaneously taking into account the material's processing and molding performance, mechanical strength, and high-temperature stability.

[0022] 3. The materials prepared by this invention have clear application scenarios, strong practicality, and significant industrial application value. The materials can be used as heat-resistant additives, reinforcing fillers, or functional modifiers, and are widely used in the field of high-temperature silicone rubber materials. They make up for the shortcomings of existing silicone rubbers, such as easy aging and decreased mechanical properties under high-temperature environments, and expand the application range of silicone rubber in high-temperature conditions (such as aerospace, electronic and electrical, chemical equipment, etc.). Compared with existing modification technologies, they have a broader application prospect. Attached Figure Description

[0023] Figure 1 This is the XRD pattern of the boron-silicon-carbon doped iron oxychloride material prepared in Example 1 of this invention.

[0024] Figure 2 This is the XPS test image of the boron-silicon-carbon doped iron oxychloride material prepared in Example 1 of this invention.

[0025] Figure 3 This is the thermogravimetric curve of the boron-silicon-carbon doped iron oxychloride material prepared in Example 1 of the present invention. Detailed Implementation

[0026] To enable those skilled in the art to better understand the technical solutions of this invention, the technical solutions will be clearly and completely described below in conjunction with the embodiments of this invention.

[0027] Example 1 The preparation method of the boron-silicon-carbon doped iron oxychloride material includes the following steps: 1) Take 1.35g of ferric chloride hexahydrate and 0.62g of phenylboronic acid, put them into a mortar and grind them thoroughly. Put the resulting mixture into a crucible. 2) Add 1.26g of diphenyldichlorosilane to the crucible and stir thoroughly with a glass rod; 3) Heat the muffle furnace to 240°C, place the crucible in the muffle furnace, and calcine for 4 hours to obtain the product boron-silicon-carbon doped iron oxychloride material.

[0028] XRD analysis was performed on the borosilicate carbon-doped iron oxychloride material, and the results are as follows: Figure 1 As shown, the measured diffraction peaks of the sample are located at 2θ≈26.12°, 35.36°, 48.12°, and 50.43°, respectively, corresponding to the FeOCl standard crystal planes (110), (021), (200), and (131), which are completely consistent with the crystal planes marked in the attached figure. The 2θ positions of all characteristic diffraction peaks are highly coincident with the standard peak positions of PDF#39-0612, with no obvious shift, proving that the main crystalline phase in the product is iron oxychloride (FeOCl). In addition, there is a gently raised diffuse scattering background in the spectrum baseline, which comes from the amorphous scattering signal of the amorphous boron-silicon-carbon doped phase in the material. This is a normal characteristic of the doped system and does not affect the determination of the FeOCl crystal phase.

[0029] XPS tests were performed on the borosilicate carbon-doped iron oxychloride material, and the results are as follows: Figure 2 As shown, the boron-silicon-carbon doped iron oxychloride material prepared in this embodiment was characterized by a full-spectrum scan using X-ray photoelectron spectroscopy (XPS). The test results are as follows. Figure 2As shown in the figure, the XPS full spectrum reveals characteristic photoelectron peaks for Fe 2p, O 1s, C 1s, B 1s, and Si 2p at their respective characteristic binding energy positions. The Fe 2p peak confirms the presence of an iron oxychloride matrix phase in the system. The simultaneous detection of the C 1s, B 1s, and Si 2p peaks demonstrates that carbon, boron, and silicon have been successfully doped into the iron oxychloride matrix, and that all elements coexist uniformly on the material surface. This indicates that the process of this invention can stably produce boron-silicon-carbon doped iron oxychloride composite target materials.

[0030] Thermogravimetric analysis was performed on the borosilicate-carbon-doped iron oxychloride material, and the results are as follows: Figure 3 As shown in the figure, the heat resistance of the material was characterized by TG-DTG thermogravimetric analysis. In the temperature range from room temperature to 800℃, the initial mass retention rate of the material was close to 100%. Below 400℃, only a slow and slight weight loss occurred, and no violent thermal decomposition was observed. A sharp characteristic thermal decomposition peak appeared only at 400℃, after which the decomposition reaction gradually tended to terminate. At a high temperature of 800℃, the material still retained nearly 80% of the residual mass, indicating that the material has a high thermal decomposition initiation temperature, a considerable high-temperature residual weight rate, excellent thermal stability and resistance to thermal degradation, and is suitable for various high-temperature applications.

[0031] Example 2 The preparation method of the boron-silicon-carbon doped iron oxychloride material includes the following steps: 1) Take 1.0g of ferrous chloride tetrahydrate and 0.62g of phenylboronic acid, put them into a mortar and grind them thoroughly. Put the resulting mixture into a crucible. 2) Add 1.26g of diphenyldichlorosilane to the crucible and stir thoroughly with a glass rod; 3) Heat the muffle furnace to 240°C, place the crucible in the muffle furnace, and calcine for 4 hours to obtain the product.

[0032] Example 3 The preparation method of the boron-silicon-carbon doped iron oxychloride material includes the following steps: 1) Take 1.35g of ferric chloride hexahydrate and 0.69g of p-methylphenylboronic acid, put them into a mortar and grind them thoroughly, and put the resulting mixture into a crucible; 2) Add 1.26g of diphenyldichlorosilane to the crucible and stir thoroughly with a glass rod; 3) Heat the muffle furnace to 240°C, place the crucible in the muffle furnace, and calcine for 4 hours to obtain the product.

[0033] Example 4 The preparation method of the boron-silicon-carbon doped iron oxychloride material includes the following steps: 1) Take 1.35g of ferric chloride hexahydrate and 0.62g of phenylboronic acid, put them into a mortar and grind them thoroughly. Put the resulting mixture into a crucible. 2) Add 1.26g of diphenyldichlorosilane to the crucible and stir thoroughly with a glass rod; 3) Heat the muffle furnace to 240°C, place the crucible in the muffle furnace, and calcine for 6 hours to obtain the product.

[0034] Example 5 The preparation method of the boron-silicon-carbon doped iron oxychloride material includes the following steps: 1) Take 1.35g of ferric chloride hexahydrate and 0.31g of phenylboronic acid, put them into a mortar and grind them thoroughly. Put the resulting mixture into a crucible. 2) Add 1.01g of diphenyldichlorosilane to the crucible and stir thoroughly with a glass rod; 3) Heat the muffle furnace to 240°C, place the crucible in the muffle furnace, and calcine for 4 hours to obtain the product.

[0035] Example 6 The preparation method of the boron-silicon-carbon doped iron oxychloride material includes the following steps: 1) Take 1.35g of ferric chloride hexahydrate and 0.93g of phenylboronic acid, put them into a mortar and grind them thoroughly. Put the resulting mixture into a crucible.

[0036] 2) Add 1.51g of diphenyldichlorosilane to the crucible and stir thoroughly with a glass rod.

[0037] 3) Heat the muffle furnace to 240°C, place the crucible in the muffle furnace, and calcine for 4 hours to obtain the product.

[0038] Comparative Example 1 Unlike Example 1, in step 3) of this comparative example, the muffle furnace is heated to 170°C, while the rest of the preparation methods and steps are the same as in Example 1.

[0039] Comparative Example 2 Unlike Example 1, in step 3) of this comparative example, the muffle furnace is heated to 290°C, while the rest of the preparation methods and steps are the same as in Example 1.

[0040] Comparative Example 3 Unlike Example 1, the calcination time in step 3) of this comparative example is 1.5 h, while the rest of the preparation methods and steps are the same as in Example 1.

[0041] Comparative Example 4 Unlike Example 1, the calcination time in step 3) of this comparative example is 9 hours, while the rest of the preparation methods and steps are the same as in Example 1.

[0042] Comparative Example 5 Unlike Example 1, this comparative example does not contain phenylboronic acid, and the preparation steps are as follows: 1) Take 1.35g of ferric chloride hexahydrate, grind it thoroughly in a mortar, and then put it into a crucible; 2) Add 1.26g of diphenyldichlorosilane to the crucible and stir thoroughly with a glass rod; 3) Heat the muffle furnace to 240°C, place the crucible in the muffle furnace, and calcine for 4 hours to obtain the product.

[0043] Comparative Example 6 Unlike Example 1, this comparative example does not contain diphenyldichlorosilane, and the preparation steps are as follows: 1) Take 1.35g of ferric chloride hexahydrate and 0.62g of phenylboronic acid, put them into a mortar and grind them thoroughly. Put the resulting mixture into a crucible. 2) Heat the muffle furnace to 240°C, place the crucible in the muffle furnace, and calcine for 4 hours to obtain the product.

[0044] Comparative Example 7 The preparation method of the boron-silicon-carbon doped iron oxychloride material includes the following steps: 1) Take 1.35g of ferric chloride hexahydrate and 0.18g of phenylboronic acid, put them into a mortar and grind them thoroughly. Put the resulting mixture into a crucible. 2) Add 1.90g of diphenyldichlorosilane to the crucible and stir thoroughly with a glass rod; 3) Heat the muffle furnace to 240°C, place the crucible in the muffle furnace, and calcine for 4 hours to obtain the product boron-silicon-carbon doped iron oxychloride material.

[0045] Comparative Example 8 The preparation method of the boron-silicon-carbon doped iron oxychloride material includes the following steps: 1) Take 1.35g of ferric chloride hexahydrate and 1.11g of phenylboronic acid, put them into a mortar and grind them thoroughly. Put the resulting mixture into a crucible. 2) Add 0.76g of diphenyldichlorosilane to the crucible and stir thoroughly with a glass rod; 3) Heat the muffle furnace to 240°C, place the crucible in the muffle furnace, and calcine for 4 hours to obtain the product boron-silicon-carbon doped iron oxychloride material.

[0046] Comparative Example 9 Unlike Example 1, this comparative example uses 0.81 g of anhydrous ferric chloride, which is an equimolar amount of ferric chloride hexahydrate. The rest of the preparation methods and steps are the same as in Example 1.

[0047] The products prepared in the above examples and comparative examples were added to silicone rubber as fillers, and performance tests were conducted after vulcanization.

[0048] The silicone rubber matrix formulation is as follows: 100 parts of α,ω-dihydroxypolydimethylsiloxane (20000 mPa·s), 12 parts of fumed silica, 6 parts of the deoxime-type crosslinking agent methyltributanone oxime silane, 0.3 parts of dibutyltin dilaurate, and 3 parts of the product from the examples and comparative examples. The preparation process of the silicone rubber includes the following steps: 1) Add α,ω-dihydroxypolydimethylsiloxane, fumed silica, and the products of the examples and comparative examples to a three-dimensional high-speed disperser and stir for 1 hour; 2) Add the deoxime-type crosslinking agent and continue stirring for 40 minutes while maintaining a pressure of -0.095 MPa; 3) Add the organotin catalyst dibutyltin dilaurate, and continue stirring for 30 minutes while maintaining a pressure of -0.095 MPa to obtain silicone rubber.

[0049] Vulcanization process: vulcanization at room temperature (25℃) and humidity (55%) for 7 days under normal pressure; The specific testing standards are as follows: Mechanical properties: GB / T 528-2009; The specimen is 2mm thick dumbbell-shaped, cured at room temperature for 7 days, and the tensile strength is tested at 500mm / min at 25℃.

[0050] Temperature resistance: GB / T 27761-2011, using a thermogravimetric analyzer, nitrogen atmosphere (50mL / min), heating rate 10℃ / min, from room temperature to 800℃, to determine the 5% thermal decomposition temperature (T5%) and the char residue at 800℃.

[0051] Thixotropy: According to ASTM D2196-2018, the viscosity at 0.5 rpm and 5 rpm was measured using a rotational viscometer at 25°C. The thixotropic index TI = η 0.5 / η 5.0 .

[0052] The performance test results of silicone rubber prepared using the products from the examples and comparative examples as fillers are shown in Table 1.

[0053]

[0054] Example 1 uses ferric chloride hexahydrate, phenylboronic acid, and diphenyldichlorosilane as raw materials, with a controlled molar ratio of 1:1:1 and calcination at 240°C for 4 hours to construct a heat-resistant skeleton with a complete structure and abundant crosslinking sites. When applied to silicone rubber modification, the composite material has the highest thermal decomposition temperature and high-temperature char rate, and its comprehensive high-temperature resistance performance is the best in this set of examples.

[0055] In Example 2, ferrous chloride tetrahydrate was used as the iron source. Ferrous ions can participate in the cross-linking reaction of the system and form an inorganic network of iron oxides. The heat resistance of the resulting hybrid filler-modified silicone rubber is better than that of the comparative example. Compared with Example 1, the high-temperature resistance has a slight gradient difference due to the difference in the catalytic activity of metal ions and the thermodynamic stability of the oxide skeleton.

[0056] Example 3 uses methylphenylboronic acid. Methyl-substituted arylboronic acid can participate in the construction of a hybrid heat-resistant skeleton. The thermal stability of the modified silicone rubber is significantly better than that of the comparative example. Due to the electronic effect, steric hindrance and thermal properties of alkyl side chains, the crosslinking density and heat resistance of the system are slightly different from those of Example 1.

[0057] In Example 4, the calcination time was adjusted to 6 hours. Extending the calcination time can fully complete the condensation and hybridization of the raw materials. The filler prepared can still impart excellent high-temperature barrier and char-forming ability to silicone rubber, and its overall temperature resistance is better than that of the comparative example. The long-term heat treatment caused a small amount of aryl carbonization and agglomeration, resulting in a slight difference in its thermal stability index compared with Example 1.

[0058] In Example 5, the lower limit of the formulation ratio was used for feeding. The system could still generate a continuous boron-iron-silicon-oxygen hybrid heat-resistant skeleton. The high temperature resistance of the modified silicone rubber was significantly better than that of the comparative example. The reduction in the amount of boron source and silicon source resulted in a decrease in the number of crosslinking active sites. The density of the hybrid skeleton was not as good as that of Example 1, and there was a certain gradient difference in heat resistance.

[0059] Example 6 uses the upper limit of the formulation ratio to prepare hybrid fillers. After the excess raw materials are mixed, the system still retains a sufficient amount of inorganic heat-resistant active components. The carbonization and heat insulation effects of the composite material are better than those of the comparative example. The excess raw materials that do not participate in crosslinking form a small amount of free components, which relatively reduces the proportion of effective heat-resistant components. The overall temperature resistance is slightly lower than that of Example 1.

[0060] In summary, the borosilicate carbon-doped iron oxychloride fillers prepared in Examples 1-6 can effectively improve the thermal decomposition temperature and high-temperature char rate of silicone rubber, and their high-temperature resistance is superior to that of the comparative examples. Due to differences in the type of iron source, boric acid substitution structure, calcination process, and raw material ratio parameters, the integrity of the hybrid skeleton and the crosslinking density of each example group are different. Among them, Example 1 is the optimal process combination.

[0061] Comparative Example 1: The calcination temperature of 170℃ is lower than the lower limit of the process, so the cross-linking reaction cannot be initiated. The product is only a physical mixture of raw materials, without an effective heat-resistant skeleton, and the temperature resistance is greatly reduced.

[0062] Comparative Example 2, with a calcination temperature of 290℃, exceeded the upper temperature limit. The high temperature completely destroyed the hybrid coordination structure, and the heat resistance function of the filler was completely lost, making it the group with the worst temperature resistance in this test.

[0063] Comparative Example 3 had a calcination time of only 1.5 hours, which was insufficient for the reaction time. As a result, the product had an extremely low degree of crosslinking, poor structural stability, and a sharp drop in the heat resistance of the silicone rubber.

[0064] Comparative Example 4 had a calcination time of 9 hours. The prolonged high temperature caused the active heat-resistant sites to become inactive and the organic groups to degrade excessively, resulting in a significant decline in the heat resistance modification effect of the filler.

[0065] Comparative Example 5 lacks phenylboronic acid raw material, which cannot form a ternary synergistic heat-resistant system and only generates a binary complex. The cross-linking system is imperfect, and the temperature resistance is significantly worse.

[0066] Comparative Example 6 lacked a diphenyldichlorosilane silicon source, making it impossible to construct a silicon-oxygen heat-resistant backbone. This resulted in decreased compatibility between the filler and the matrix, and a significant reduction in high-temperature stability.

[0067] In Comparative Example 7, the raw material ratio was unbalanced, with insufficient boric acid and excessive silane. The coordination balance of the system was broken, the internal phase separation of the filler was severe, the structural defects increased, and the temperature resistance was greatly deteriorated.

[0068] In Comparative Example 8, there was an excess of boric acid and an insufficient silicon source. The decomposition of the excess boric acid produced pore defects, resulting in an incomplete silicon-oxygen framework. After filling, the internal defects of the compound were aggravated, and the temperature resistance was much worse than that of Example 1.

[0069] Comparative Example 9 Using ferric chloride without crystallization water, the product's heat resistance is significantly weaker than that of the product prepared by ferric chloride hexahydrate because crystallization water can create a trace liquid phase mass transfer environment, reduce the reaction activation energy, promote uniform doping of borosilicate carbon and build a stable porous framework.

[0070] Based on the above examples and comparative test results, it can be seen that the synergistic combination of raw material types, proportion ranges, calcination temperatures, and calcination times specified in this invention is key to preparing high-performance borosilicate-carbon doped iron oxychloride fillers. The process parameters corresponding to Example 1 represent the optimal implementation scheme of this invention. The hybrid filler prepared by this process can impart optimal high-temperature resistance, thermal insulation, and charring properties to silicone rubber without compromising its original mechanical properties and thixotropic characteristics.

[0071] Although the present invention has been described in detail by way of preferred embodiments, the invention is not limited thereto. Various equivalent modifications or substitutions can be made to the embodiments of the present invention by those skilled in the art without departing from the spirit and essence of the invention, and such modifications or substitutions should all be within the scope of the invention. Therefore, the scope of protection of the present invention should be determined by the scope of the claims.

Claims

1. A method for preparing boron-silicon-carbon doped iron oxychloride material, characterized in that, Includes the following steps: 1) Take iron-based chloride and organoboronic acid compounds, grind and mix them evenly, and put the evenly mixed material into the reactor; 2) Add phenylchlorosilane to the reactor and stir to mix thoroughly; 3) Calcine the mixed materials from step 2) to obtain boron-silicon-carbon doped iron oxychloride material.

2. The preparation method of boron-silicon-carbon doped iron oxychloride material as described in claim 1, characterized in that, The molar ratio of the iron-based chloride, organoboronic acid compound, and phenylchlorosilane is 1:(0.5-1.6):(0.8-1.2).

3. The preparation method of boron-silicon-carbon doped iron oxychloride material as described in claim 1, characterized in that, The iron-based chloride is ferric chloride hexahydrate or ferrous chloride tetrahydrate.

4. The preparation method of boron-silicon-carbon doped iron oxychloride material as described in claim 1, characterized in that, The organoboronic acid compound is one of phenylboronic acid, p-methylphenylboronic acid, and naphthaleneboronic acid.

5. The method for preparing boron-silicon-carbon doped iron oxychloride material as described in claim 1, characterized in that, The phenylchlorosilane is one of diphenyldichlorosilane, phenyltrichlorosilane, and methylphenyldichlorosilane.

6. The method for preparing boron-silicon-carbon doped iron oxychloride material as described in claim 1, characterized in that, In step 3), the calcination temperature is 180-280℃ and the time is 2-8h.

7. The method for preparing boron-silicon-carbon doped iron oxychloride material as described in claim 1, characterized in that, In step 3), the calcination temperature is 230-250℃ and the time is 4-6h.

8. The boron-silicon-carbon doped iron oxychloride material prepared by the preparation method according to any one of claims 1-7.

9. The application of the boron-silicon-carbon doped iron oxychloride material as described in claim 8 in silicone rubber.

Citation Information

Patent Citations

  • A high-strength ablation-resistant silicone rubber and its preparation method

    CN114958001B

  • Borosiloxane polymer as well as preparation method and application thereof in silicone rubber self-adhesive tape

    CN115838477A